PENGARUH SIKAP BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VIII DI SMP NEGERI 3 KAMPAR KIRI TENGAH - Nuraida Nuraida; Srikartikowati Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of learning attitudes and learning motivation on the students learning achievement of Class VIII SMP Negeri 3 Kampar Kiri Tengah. Data collection techniques were carried out by documentation to obtain student learning achievement and using questionnaires to obtain data on learning attitudes and learning motivation. The population used in this study were all students of class VIII SMP Negeri 3 Kampar Kiri Tengah, amounting to 103 people. The entire population is examined (census). The collected data is then tabulated and analyzed using multiple linear regression with SPSS version 24. Based on the results of data analysis, it is known that there is a positive effect on learning attitudes towards learning achievement which is equal to 0.3481 or 34.81 %, there is a positive effect of learning motivation on learning achievement which is equal to 0.8760 or 87.60 %. R Square values obtained is 0.393. This means that student learning outcomes can be influenced by independent variables namely learning attitudes and learning motivation by 39.3%, while the remaining 61.7% is influenced by other variables not examined.Key Words: Learning Attitudes, Learning Motivation, Students Learning Achievement.